Animal dreams : a novel - Kingsolver, Barbara (New York : HarperPerennial, 1991)
Codi returns to her hometown to confront her past and face her ailing father. What she finds is a town threatened by an environmental catastrophe and a man who could change her life.
Wilson's Fiction.
Young Adult
Keywords: Self-perception -- Fiction; Self-perception -- Fiction